2000
DOI: 10.1007/s100640000051
|View full text |Cite
|
Sign up to set email alerts
|

A geological model of the buried Tiber River valley beneath the historical centre of Rome

Abstract: The study develops a geological/geotechnical model of the filling of the buried Tiber River valley in the area of Rome. The approach has been multidisciplinary: the fill sediments have been analysed in detail and are given on a cross section based on either the observations of 57 borehole cores and/or the laboratory tests on various types of samples. Information regarding the geology, geomorphology, climate, hydrographic network, urban development and history of the Rome area has been used to interpret this se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…The change in climatic conditions provoked the glaciers to melt, a fast sea level rise (Bard et al 1996) and the fluvial valleys to be filled by alluvia. The sediments deposited during Holocene within the valleys are generally characterized by a fining-upward succession, with a relatively thin horizon of gravel at the base, grading upward into a thick pack of sand and clay (Bozzano et al 2000). Within this sedimentary body the intercalations of organic material such as carbonized plants and peat horizons are frequent.…”
Section: Geological Settingmentioning
confidence: 98%
See 1 more Smart Citation
“…The change in climatic conditions provoked the glaciers to melt, a fast sea level rise (Bard et al 1996) and the fluvial valleys to be filled by alluvia. The sediments deposited during Holocene within the valleys are generally characterized by a fining-upward succession, with a relatively thin horizon of gravel at the base, grading upward into a thick pack of sand and clay (Bozzano et al 2000). Within this sedimentary body the intercalations of organic material such as carbonized plants and peat horizons are frequent.…”
Section: Geological Settingmentioning
confidence: 98%
“…Within this sedimentary body the intercalations of organic material such as carbonized plants and peat horizons are frequent. Therefore, the alluvial deposits are generally characterised as low consistency, saturated, fine-grained soils from normally consolidated to weakly over consolidated in the superficial part and generally characterized by low stiffness parameter values (Bozzano et al 2000).…”
Section: Geological Settingmentioning
confidence: 99%
“…From a general point of view, for unconventional and historical structures like the Colosseum, the simplified approach suggested by the NTC08 for soil classification is not adequate and specific studies are needed to build a truly representative model of the subsoil and the buried part of the structure. Bozzano et al [2000], Bozzano et al [2008] and Caserta et al [2012] investigated the different lithotypes constituting the recent sedimentary fill of the Holocene Tiber River Valley under both static and dynamic conditions. Bianchi Fasani et al [2013] reported the typical ranges of shear-wave velocities observed in situ for the pyroclastic units within Rome city.…”
Section: Site Description and Geological Backgroundmentioning
confidence: 99%
“…Even the most accurate measurement currently possible (given the impossibility of astronomical measurement in an underground environment) would have an accuracy of a few dozen arc seconds. A possible cause of eventual change of the original azimuth of the track is a differential settlement due to the alluvial nature of the ground (Bozzano et al 2000;Camponeschi and Nolasco 1982). Geodynamic movements since antiquity of the sundial's meridian line presumably do not significantly influence the azimuth itself, while an accurate evaluation of geodynamic rotations would require a further study, both for the choice of the correct model and reference De Mets (2013), as well as in function of the specific movements of the Italian peninsula (Devoti et al 2014).…”
Section: Final Remarks and Unresolved Issuesmentioning
confidence: 99%